End-to-end delay differentiation of IP traffic aggregates using priority queuing models - Sousa, Pedro (2002)
This article evaluates the use of Priority Queuing (PQ) Models to achieve delay differentiation in networks operating under the Class of Services paradigm. Three PQ variants are considered: the proportional model, the additive model and a novel hybrid schema based on the upper time limit model. Through appropriate queueing and scheduling, delay differentiation is first considered for a node, and then extended to an end-to-end perspective. For each model, the corresponding delay differentiation bounds are determined and verified resorting to simulation.